Embodiment and simulated interaction in online stance expression - Dancygier, Barbara; Vandelanotte, Lieven (Frontiers in Psychology, 2025)
The expression and exchange of stance drives much social media discourse, including internet memes. We demonstrate how, even in the absence of actual face-to-face communication, online discourse and memes rely on the dynamics of embodiment and dialogue in comparable ways, while also developing specific constructional forms for this with no direct face-to-face equivalent. We introduce the notion of simulated interaction to refer to the combinations of embodied expression, images, and the structures of (apparent) quotation and dialogue allowing online communicators to vividly represent experience and signal stance.